2018
DOI: 10.1371/journal.pone.0203322
|View full text |Cite
|
Sign up to set email alerts
|

Correlating blood-based DNA methylation markers and prostate cancer risk in African-American men

Abstract: The objective of this work was to investigate the clinical significance of promoter gene DNA methylation changes in whole blood from African-American (AA) men with prostate cancer (PCa). We used high throughput pyrosequencing analysis to quantify percentage DNA methylation levels in a panel of 8 genes (RARβ2, TIMP3, SPARC, CDH13, HIN1, LINE1, CYB5R2 and DRD2) in blood DNA obtained from PCa and non-cancerous controls cases. Correlations of methylation status and various clinicopathological features were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…We found that the SPARC gene promoter region was not methylated in the GES-1 cell line but found that the other four GC cell lines showed methylation. Similar conclusions were previously reported for pancreatic cancer[22], prostate cancer[23], and colon cancer[24]. These results also revealed that the methylation frequency of SPARC was positively associated with TNM stage, macroscopic type, and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the SPARC gene promoter region was not methylated in the GES-1 cell line but found that the other four GC cell lines showed methylation. Similar conclusions were previously reported for pancreatic cancer[22], prostate cancer[23], and colon cancer[24]. These results also revealed that the methylation frequency of SPARC was positively associated with TNM stage, macroscopic type, and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…A study investigating clinical significance of gene promoter DNA methylation in blood DNA found six genes promoter methylation of PCa patients to be significantly different from controls [38]. However, we did not see such differences which could be due to several reasons; firstly, T cells DNA was used in our study while blood DNA was used in previous study [38]; secondly, previous study was carried out in African American men while our study had mostly Caucasian men [38]. Also, using whole blood DNA, no association between the DNA methylation on all CG sites and risk of PCa or aggressive disease was observed [39].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer (PCa) is a complex disease, with risk factors and outcomes influenced by a combination of socioeconomic status, access to care (AtC) and quality of care (QoC) delivery, lifestyle factors, variations in inherited genetics and molecular tumor profiles (biology), as well as epigenetics [1][2][3][4][5]. In the USA, Black men are approximately 80% more likely to be diagnosed with and 220% more likely to die from PCa in comparison to White men [6].…”
Section: Introductionmentioning
confidence: 99%